Examining the sexual function and related attitudes among aged women: A cross- sectional study - Safieh Jamali; Afifeh Rahmanian; Shohreh Javadpour (Shahid Sadoughi University of Medical Science, Yazd, Iran, 2016)
Background: Sexual function and its subsequent satisfaction are among the most important aspects of women's life. However, this instinct could be influenced by some factors such as diseases, drug using, aging, and hormonal and physiologic changes associated with menopause, and sexual behavior. Objective: The aim of this study was to describe the prevalence rates of sexual dysfunction, and related attitudes among aged women in Jahrom, Iran. Materials and Methods: This cross-sectional study was conducted on 746 postmenopausal women aged between 50 and 89 years old who had referred to obstetric and gynecologic clinic in Jahrom, from April to October 2014. Female Sexual Function Index questionnaire was used order to assess the sexual function. The cases were classified into three categories according to the attitude scores: negative (17-32), medium (33-38), and positive (39-48). One-way ANOVA test was used to determine the relationship between FSFI and attitude scores. Results: The participants' mean±SD age was 60.10±6.89 years and the total mean score of FSFI was 19.31±8.5. In addition, 81.5% of the women had sexual dysfunction (FSFI< 26.55) and only 147 women (18.5%) had normal sexual function (FSFI> 26.55). Almost 62.1% the women displayed a negative attitude towards sexuality and only 18.8% women had positive attitude. Feeling of dyspareunia (p= 0.02), lubrication (p< 0.0001), orgasm (p= 0.002) and satisfaction (p= 0.002) were significantly different between three categories of attitudes regarding sexuality, respectively Conclusion: Our data showed that sexual disorders were highly prevalent among postmenopausal women. The most affected problems were arousal, dyspareunia, and lubrication. More than half of the women had negative attitude towards sexual function consequently this could affect their sexual function. So, it seems screening of sexual dysfunction for finding the causes in women should be the main sexual health program. Also, it would be important to emphasis the role of physicians and experts on education and counseling in this subject.